Mapping the Leading Livestock Sector in Musi Rawas Regency - Humaidi, Edy; Desfaryani, Rini; Windu Kertayoga, I Putu Ajie (Department of Agribusiness, Halu Oleo University, 2022)
This research attempts to identify the livestock industry in Musi Rawas Regency that can be improved. The Location Quotient (LQ) approach assesses which livestock industry leads and which is not. Secondary data from the Central Statistics Agency and the Department of Agriculture and Livestock in Musi Rawas Regency in 2019 were combined with primary data from farmer interviews. The findings revealed that six were the most popular of the nine livestock sectors: beef cattle, buffalo, goats, sheep, native chickens, ducks/ducks, dairy cattle, pigs, and broilers. The other three, dairy cattle, pigs, and broilers, were non-seeded animals